Communicating dosage instructions across cultural and linguistic barriers: Pharmacist-patient interactions in a South African antiretroviral clinic - Watermeyer, Jennifer; Penn, Claire (Stellenbosch Papers in Linguistics Plus, 2012)
No abstract available.